The Socio-spatial stratagems of human capital development in the Southern Federal Districts of Russia - G. Mabiala; D. V. Linskiy; E. A. Maslich; I. V. Bairakova; E. V. Romaniuk (Модернизация, инновация, развитие, 2023)
Purpose: is to substantiate promising strategies for sustainable development of human capital in the current conditions of the demographic crisis on the basis of scientific generalization of key social and spatial aspects of the formation, use and accumulation of human capital.Methods: the application of expert-rating methods based on the Lorentz curve and the Gini index to determine the reasons for the disparities in personal income is done in addition to the use of conventional and specific approaches.Results: the research examines the existing situation of human capital and defines strategic means of promoting its growth. The findings of the analysis of trends in human development parameters, which are one of the factors ensuring macroeconomic growth and competitiveness in the South Federal Districts of Russia and should be based on various socio-spatial development strategies, are presented. A self-sufficient socio-spatial-economic system and human capital, which provide competitive advantages, are the foundations of sustainable economic development. The key factors influencing the state of human capital and the trends of its integral indicators show low rates of socio-spatial development.Conclusions and Relevance: the research findings revealed certain negative tendencies in human capital indicators, which point to the necessity for rethinking and additional inventive adjustments to the system of social and spatial management. The work-out of mechanisms for the regulation of imbalances in its development, reversing trends in the narrowing of the labour market, developing socio-spatial programs for institutional support and regulation of labour migration, and spatial human development are among the strategies for human capital that are proposed as the top priorities